1988
DOI: 10.1161/01.cir.78.3.684
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of depressed conduction from long-term amiodarone therapy in canine myocardium.

Abstract: Amiodarone therapy leads to a significant impairment in myocardial conduction, yet it causes only a modest decrease in the maximum rate of depolarization of the action potential (dV/dT). To determine whether the decrease in dV/dT solely accounts for the impaired myocardial conduction or whether passive membrane properties may also be involved, we studied 21 ventricular epicardial tissues from 14 beagles; six dogs received long-term treatment (3-6 weeks) of amiodarone orally, and the remaining dogs served as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Both acute and chronic amiodarone prolong ERP more than APD, due to development of PRR 12,13. While acute amiodarone reduces V max and blocks I Na in practically all studies,4 chronic amiodarone was reported to either depress V max 14, 15 or, in most studies, to cause no or little changes in V max in superfused ventricular muscle and Purkinje fibers 4,16. Ventricular CV is slowed and QRS duration is prolonged in both acutely and chronically amiodarone-treated humans and animals in vivo 16-18.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both acute and chronic amiodarone prolong ERP more than APD, due to development of PRR 12,13. While acute amiodarone reduces V max and blocks I Na in practically all studies,4 chronic amiodarone was reported to either depress V max 14, 15 or, in most studies, to cause no or little changes in V max in superfused ventricular muscle and Purkinje fibers 4,16. Ventricular CV is slowed and QRS duration is prolonged in both acutely and chronically amiodarone-treated humans and animals in vivo 16-18.…”
Section: Discussionmentioning
confidence: 98%
“…While acute amiodarone reduces V max and blocks I Na in practically all studies,4 chronic amiodarone was reported to either depress V max 14, 15 or, in most studies, to cause no or little changes in V max in superfused ventricular muscle and Purkinje fibers 4,16. Ventricular CV is slowed and QRS duration is prolonged in both acutely and chronically amiodarone-treated humans and animals in vivo 16-18. However, the QRS interval was significantly prolonged only at relatively rapid pacing rates (e.g., at CL of ≤ 500 ms in humans), displaying a non-statistically significant prolongation at normal or slow heart rates,18 consistent with our results in the dog.…”
Section: Discussionmentioning
confidence: 99%
“…Both acute and chronic amiodarone have been shown to prolong the effective refractory period more than APD, resulting in post-repolarization refractoriness (PRR) 16,17. While acute amiodarone reduces V max and blocks I Na in practically all studies (for review see13), chronic amiodarone has been reported to either depress V max 9,1820 or to cause little to no change in V max in superfused ventricular muscle and Purkinje fibers 13,15,21. Ventricular conduction velocity is slowed and QRS duration is prolonged in both acute and chronic amiodarone-treated humans and animals in vivo 2123…”
Section: Discussionmentioning
confidence: 99%
“…Both acute and chronic amiodarone prolong the effective refractory period more than APD, due to development of postrepolarization refractoriness 24,25. Whereas acute amiodarone reduces V max and blocks I Na in practically all studies (for review see1), chronic amiodarone was reported to either depress V max 26,27 or, in most studies, to cause no or little changes in V max in superfused ventricular muscle and Purkinje fibers 1,21,28. Ventricular conduction velocity is slowed and QRS duration is prolonged in both acute and chronic amiodarone-treated humans and animals in vivo 28-30.…”
Section: Discussionmentioning
confidence: 99%